Microarray analysis using a limited amount of cells - Peterková, Martina; Krontorád Koutná, Irena; Tesařová, Lenka; Potěšilová, M; Kozubek, Michal; Hrabčáková, Viera; Klabusay, Martin; Doubek, Michael; Mayer, Jiří (Folia biologica (Praha), 2009)
cDNA microarray technology is widely used in various biological and medical disciplines to determine gene expression profiles. Unfortunately, this technology requires a large quantity of input RNA. Since there is an increasing need for more precise analyses of defined cell subpopulations with low cell counts, working protocols using a minimal number of input cells are required. Optimal RNA isolation and its accurate amplification are crucial to the success of these protocols. The HL-60 cell line was used in the search for a suitable protocol that can be used for clinical samples of CD34+ haematopoietic cells obtained from bone marrow. The goal was to discover the best method for isolating and amplifying RNA from a small number of cells. Our evaluation of various methods and kits available in the market revealed that the combination of RNAqueous™ Kit for RNA isolation and the SenseAmp Plus Kit for one-round RNA amplification produced the best results. This article presents a verified protocol describing a reliable and reproducible method for obtaining enough input RNA for microarray experiments when the number of cells is limited.
Keywords: HL-60 buňky; HL-60 Cells; kultivované buňky; Nucleic Acid Amplification Techniques; Financing, Organized; RNA; Cells, Cultured; financování organizované; Oligonucleotide Array Sequence Analysis; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Humans; lidé; techniky amplifikace nukleových kyselin